Factors associated with attendance at clinical follow-up of a cohort with screen-detected type 2 diabetes: ADDITION-Denmark. Issue 3 (June 2020) - Jensen, Annette Danielsen; Andersen, Signe Toft; Charles, Morten; Bjerg, Lasse; Witte, Daniel Rinse; Gram, Bibi; Jørgensen, Marit Eika; Sandbæk, Annelli; Dalsgaard, Else-Marie
Highlights: Concurrent high overall burden of disease associated with lower attendance. Concurrent cardiovascular disease did not associate with attendance in follow-up. Concurrent cancer did not associate with attendance in clinical follow-up. Concurrent poor self-rated health did not associate with attendance in follow-up. Concurrent HbA1c levels did not associate with attendance in clinical follow-up. Abstract: Aims: To determine the association between concurrent overall burden of disease, cardiovascular disease, cancer, self-rated health, HbA1c levels, and attendance at clinical follow-up of the Danish arm of the ADDITION-study. Methods: Logistic regression models were used to study factors proposed being associated with attendance in clinical follow-up. We used data from clinical examinations, questionnaires and national registers at a time-point near the follow-up examination. Results: A total of 1119 participants were eligible for the follow-up conducted a median of 12.8 years (IQR 11.6; 13.4) after type 2 diabetes diagnosis by screening. Concurrent high burden of disease was associated with lower attendance (OR 0.6 (95% CI: 0.4; 0.9) for high-versus no burden of disease). Concurrent cardiovascular disease and cancer showed no statistically significant association with attendance (OR 1.0 (95% CI: 0.7; 1.4)) and (OR 0.8 (95% CI: 0.6; 1.1) for (disease versus no disease). Similarly, self-rated health (OR 0.7 (95% CI: 0.5; 1.0) poor-versus good self-rated health) and HbA1c levels (OR 1.0 (95% CI: 0.9; 1.2 unit = 10 mmol/mol)) were not statistically significant associated with attendance. Conclusions: This study showed a lower attendance in clinical follow-up after nearly 13 years among individuals with concurrent high burden of disease. No associations were found between concurrent CVD, cancer, self-rated health and Hba1c levels and attendance.